Impact of Recession on Maintaining the Sustainability of Acute Care Hospitals - Costello, Michael M.; West, Daniel J.; Ramirez, Bernardo (Recent Research Advances in Arts and Social Studies Vol. 7, 2024)
The present study highlights about the impact of Recession on maintaining the sustainability of acute care hospitals. The concern over rapidly increasing hospital costs has led many nations that previously favored government owner- ship of hospitals to consider privatization with the goal of reducing government expenditures associated with hospital ownership. Governments are closely monitoring hospital privatization as a strategy to curb cost growth, given the importance of hospital expenses as a percentage of a country's overall health care expenditures. Although the process of privatization may vary from country to country, these changes entail the application of market forces to the availability and provision of healthcare services. Correspondingly, nations must determine whether market forces alone should determine whether specific hospitals should be allowed to close based upon the owner’s sole determination. Responses to the financial crisis of 2007-2009 show that government intervention preserved several financial institutions whose closure or bankruptcy would have meant the termination of critical financial services. The authors believe that such intervention can be rationalized in certain cases of potential acute care hospital closures. Several international examples of health policies intended to maintain government involvement after hospital privatization are included. Governmental officials and health system managers must look carefully at sustainability strategies and health management educators must emphasize key competencies necessary to manage system change effectively. Policy makers must carefully consider governmental sustainability initiatives to limit worldwide competitive market forces as the sole determinants of acute hospital access.